A systematic review of interventions aiming to improve communication of prognosis to adult patients. Issue 8 (August 2020) - Selim, Shehab; Kunkel, Elizabeth; Wegier, Pete; Tanuseputro, Peter; Downar, James; Isenberg, Sarina R.; Li, Aimee; Kyeremanteng, Kwadwo; Manuel, Douglas; Kobewka, Daniel M.
Highlights: Interventions on prognosis delivery have not been studied in isolation and so the effect is unknown Education for doctors that includes teaching about prognosis can improve patient reported outcomes A question prompt list with questions about prognosis helps patients ask about prognosis Abstract: Objective: Our objective was to describe interventions that aim to improve communication of prognosis to adult patients and to summarize the effect of interventions. Methods: We included randomized controlled trials of interventions that included prognosis delivery. We excluded studies of decision aids. Our analysis was a narrative synthesis of interventions and outcomes. Results: Our search identified 1151 unique records. After screening, and full text review we included 21 reports from 17 RCTs. Only 2 studies used a prediction model to generate prognostic estimates. Four studies used education, ten used patient mediated interventions, and 2 used coordination of care. In some studies education that includes prognosis improves patient reported outcomes, communication and treatment decisions, patient mediated interventions can increase the number of questions patients ask about prognosis. Coordination of care may improve satisfaction. Conclusions: Education for clinicians that includes teaching about how to communicate prognosis may improve patient reported outcomes. Patient mediated interventions can increase the number of prognosis related questions asked by patients. Practice Implications: Communication skills training that includes training on delivering prognosis may improve communication and patient reported outcomes, but the evidence is uncertain. Giving patients question prompt lists can help them ask more prognosis related questions.